A família Bromeliaceae nas restingas do estado do Rio de Janeiro: fitogeografia - Moura, Ricardo Loyola de (2002)
The Bromeliaceae have some 2750 species distributed throughout tropical and subtropical America, and one species of Pitcairnia in western Africa. ln the Americas, this family ranges from the United States to Chile and Argentina. Approximately 60 species are found on the sandy coastal plains (restingas) of Rio de Janeiro State. Floristic surveys of several sandy coastal plains along the Brazilian coast from Bahia to Santa Catarina show that this family is one of the 10 most important in terms of species richness in this habitat. The aims of this study are to update the distribution ranges of these species and comment on disjunct, restricted and endemic distribution patterns, thus contributing to a broader understanding of bromeliad phytogeography. Data are presented that will help to solve the taxonomic problems of some species and also conserve ecologically important areas. A vast amount of information on the distribution of the species studied here was obtained from Brazilian and foreign herbaria, as well as the literature. These data were plotted on maps, providing a more complete distribution of several species such as, for example, Tillandsia recurvata. The distribution patterns of the taxons are discussed. More detailed studies are needed to provide a better understanding of the phytogeography of this family.